Brief communication: Accurate and autonomous snow water equivalent measurements using a cosmic ray sensor on a Himalayan glacier - N. Pokhrel; N. Pokhrel; P. Wagnon; F. Brun; A. Khadka; A. Khadka; A. Khadka; T. Matthews; A. Goutard; D. Shrestha; B. Perry; M. Réveillet (The Cryosphere)
We analyze snow water equivalent (SWE) measurements from a cosmic ray sensor (CRS) on the lower accumulation area of Mera Glacier (central Himalaya, Nepal) between November 2019 and November 2021. The CRS aligned well with field observations and revealed accumulation in pre-monsoon and monsoon observations, followed by ablation in post-monsoon and winter observations. COSIPY simulations suggest significant surface melting, water percolation, and refreezing within the snowpack, consistent with CRS observations yet liable to be missed by surface mass balance surveys. We conclude that CRS can be used to determine mass fluxes in various climatic settings, but the interpretation of the total changes in SWE needs complementary measurements and model analysis to determine the share of specific mass fluxes, such as melt and refreezing.